Implementation Of SDG 16.1: Analysis Of Ghana’s Efforts To Reduce Sexual Violence - Achempong, D. (University Of Ghana, 2022)
Sexual violence has been classified as a public health problem which happens in various forms and context such as rape, unwanted sexual advances, sexual abuse of vulnerable people, forced marriage or cohabitation, among others. Despite numerous existing instruments, sexual violence still persists, necessitating a more comprehensive guide in 2015 as part of the Sustainable Development Goals (SDGs). Target 16.1 of the SDGs specifically seeks to reduce all forms of violence and its related deaths in the world. To achieve this target, some states have designed specific instruments and programmes aimed at reducing sexual violence by 2030, and these frameworks have been tailored into their national policies. To investigate the specific interventions being implemented by Ghana after the SDGs and the progress made so far, this study was conducted using qualitative research methodology. Semi-structured interviews were conducted with selected persons from key institutions such as DOVVSU, CHRAJ, UNFPA, UNICEF and Ark Foundation, as well as with victims of sexual violence. Findings show that before 2015, Ghana has been signatory to seventeen existing international instruments that prohibits sexual violence and has therefore translated some of these legal instruments into national policies and created institutions to spearhead their implementation. After the SDGs were adopted, more instruments and policies have been implemented in the short and medium term to further reduce sexual violence by 2030. The study reveals that recent legislations and commitments towards reducing sexual violence by 2030 are more pronounced than before as more resources have been committed towards this course especially by intergovernmental organizations (IGOs) and nongovernmental organizations (NGOs). Despite the various efforts, the study identified that new initiatives and policies spearheaded by government are not as progressive as anticipated due to inadequate financial commitments. Meanwhile, initiatives and programs steered by IGOs and NGOs are progressive due to adequate resource allocations and financial commitments. The study concludes that commendable strides have been made from 2015 to 2021 towards reducing sexual violence in Ghana through existing institutions, policies and legal frameworks, but more could be achieved. The study therefore recommends that government should make adequate financial commitment towards gender-related issues, must cut unnecessary bureaucratic processes that impede contributions of development partners and should revise some existing instruments to meet current standards.
M.A. International Affairs
Keywords: SDG 16.1; Ghana; Sexual Violence